ATRIBUTOS FÍSICOS E TEOR DE MATÉRIA ORGÂNICA EM ARGISSOLO VERMELHO SOB DIFERENTES SISTEMAS DE MANEJO - Monson, Kelvin; Monteiro, Felipe; Falcão, Karina; Da Silva, Roniedison; Sotolani, Bruno; Panachuki, Eloi (ANAIS DO ENIC, 2018)
-